THE INFLUENCE OF NONPHYSICAL WORK ENVIRONMENT, WORKLOAD AND JOB SATISFACTION ON EMPOLOYEE TURNOVER INTENTION PT. UTAMA FINANCE CIKARANG - Fitri Rezeki; Ni Desak Made Santi Diwyarthi; Fachrurazi Fachrurazi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Erratic business competition makes human resources the most important thing to realize a stable economy to make companies able to compete sustainably. Companies are required to have a more optimal, stable and creative performance in their business competition. A good company is largely determined by the human resources owned by a company. The main objective of this study is to measure how much impact the resulting from the variables of the nonphysical work environment, workload and job satisfaction on turnover intention. This type of research uses statistical analysis methods assisted by SPSS Version 24 data processing software. This sampling used a random sempel technique with a total of 80 respondents. This study aims to test, study, and also obtain results on how the influence of non-interpretation work environment, workload and satisfaction on turnover intention in PT. Utama Finance Cikarang. The results of this study show that: (1) there is a positive and significant influence on the nonphysical work environment with the Turnover intention of PT. Main Finance Cikarang. (2) there is no positive and significant effect on workload with Turnover intention PT. Utama Finance Cikarang. (3) there is a positive and significant influence on job satisfaction with PT.Utama Finance Cikarang.